Psychological Factors Related to Fear of COVID-19 in the General Salvadoran Population - Lobos Rivera, Marlon Elías (2022)
Introduction: The objective of this article is to determine the psychological factors which are associated with the fear toward COVID-19 as experienced by the Salvadoran population in general. Method: This study is exploratory, with a cross-sectional design. For data collection a digital survey in Google Forms was used. There was a non-probabilistic sample of 328 Salvadorans. The mean age in general was 27.90 years-old, with a standard deviation (SD) of 9.10; the mean age for men was 29.05 years-old (SD = 9.94), and the mean age for woman was 27.42 years-old (SD = 8.70). Results: The results reveal the existence of small and medium correlations between anxiety, depression, instrumental support and positive social interaction with the variables of fear to COVID-19; the regression model predicted that the fear to COVID-19 depends on anxiety and affective support, predicting a 23% of fear to COVID-19, with medium effect. Conclusion: This research suggests anxiety and affective support are explanation of the 23% of fear towards COVID-19 in Salvadoran population in general, findings provide useful information for future researches which perform a follow up or intervention in Salvadoran population in general.